The Effectiveness of using National Values in the Educational and Upbringing Process (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the theoretical and practical aspects of applying national values in the educational and upbringing process. It analyzes the pedagogical views of prominent scholars such as Al-Farabi, Ibn Sina (Avicenna), Alisher Navoi, and Abdulla Avloni, highlighting their relevance to contemporary educational practices. The article also examines how the integration of national values fosters spiritual maturity, patriotism, national identity, and social cohesion among the younger generation. In the context of globalization, utilizing national values in education is considered an effective tool to preserve cultural identity while ensuring the comprehensive development of youth.